Investigation of a flame spray pyrolysis process using several optical measurement techniques - Münsterjohann, Bettina; Huber, Franz; Stanzel, Melanie; Peukert, Wolfgang; Will, Stefan (International Congress Engineering of Advanced Materials, 2017)
The flame spray pyrolysis (FSP) process is one of the mostly used gas-phase techniques in industry and research to produce a broad spectrum of complex and functional nanoparticles on acommercial scale. Nanoparticulate oxides, including zinc oxide (ZnO), gallium(III)-oxide (Ga2O3) or indium(III)-oxide (In2O3) are low cost and promising materials for electronic and optical devices. To cover the high demand of these interesting materials, FSP turned out to be an economic, energy- and cost-efficient syntheses method. In the flame droplet formation, evaporation, combustion, nanoparticle formation and finally particle growth, agglomeration and sintering takes place. For the production of nanoparticles with well-defined properties, a detailed understanding of the interplay between these different particle formation steps and the influence of varying process conditions on the resulting nanoparticles is essential. However, due to the highly turbulent and multiphase character of the spray flame it is still limited.As the droplet formation and evaporation is one of the first crucial steps in the FSP process, it was characterized by Mie-scattering, Phase-Doppler Anemometry (PDA) and shadowgraphymeasurements under different process conditions. PDA allows for pointwise droplet velocity and droplet size measurements whereas the spray geometry with its spray angle and height was analyzed by shadowgraphy measurements and Mie-scattering. The ethanol spray was investigatedat both conditions with and without a flame so that the influence of evaporation and combustion on the droplet formation can be analyzed. In order to localize the nucleation zone where particle formation takes place, chemiluminescence measurements were performed for different material systems like pure metal oxides (ZnO, TiO2, SnO, Ga2O3, In2O3) and mixed oxides (ITO, indium zinc oxide, gallium zinc oxide). Furthermore the influence of varying precursor flow rates (2.5 l/min to 10 l/min) and precursor concentrations (0.1 mol/l to 0.5 mol/l) on the size and location of the nucleation zone was investigated. As temperature is one of the most important factors influencing particle size, morphology and crystallinity initial tests for measurements of temperature fields by Two-Line Atomic Fluorescence (TLAF) were performed. Finally, the sizes of the aggregates formed were determined by wide-angle light scattering (WALS
Keywords: PDA; shadowgraphy; Mie-scattering; chemiluminescence; TLAF; WALS